The GALAH survey and Gaia DR2: dissecting the stellar disc's phase space by age, action, chemistry, and location. Issue 1 (22nd January 2019) - Bland-Hawthorn, Joss; Sharma, Sanjib; Tepper-Garcia, Thor; Binney, James; Freeman, Ken C; Hayden, Michael R; Kos, Janez; De Silva, Gayandhi M; Ellis, Simon; Lewis, Geraint F; Asplund, Martin; Buder, Sven; et al.
Abstract: We use the second data releases of the European Space Agency Gaia astrometric survey and the high-resolution Galactic Archaeology with HERMES (GALAH) spectroscopic survey to analyse the structure of our Galaxy's disc components. With GALAH, we separate the α-rich and α-poor discs (with respect to Fe), which are superposed in both position and velocity space, and examine their distributions in action space. We study the distribution of stars in the zV $ z$ phase plane, for both V ϕ and VR, and recover the remarkable 'phase spiral' discovered by Gaia . We identify the anticipated quadrupole signature in zV $ z$ of a tilted velocity ellipsoid for stars above and below the Galactic plane. By connecting our work with earlier studies, we show that the phase spiral is likely to extend well beyond the narrow solar neighbourhood cylinder in which it was found. The phase spiral is a signature of corrugated waves that propagate through the disc, and the associated non-equilibrium phase mixing. The radially asymmetric distribution of stars involved in the phase spiral reveals that the corrugation, which is mostly confined to the α-poor disc, grows in z -amplitude with increasing radius. We present new simulations of tidal disturbance of the Galactic disc by the Sagittarius (Sgr) dwarf. The effect on the zV $ z$ phase plane lasts ${\gtrsim } 2\, Gyr$, but a subsequent disc crossing wipes out the coherent structure. We find that the phase spiral was excited ${\lesssim } 0.5\, Gyr$ ago by an object like Sgr with total mass ∼3 × 10 10 M⊙ (stripped down from ∼5 × 10 10 M⊙ when it first entered the halo) passing through the plane.